Recent Discoveries in Evolutionary and Genomic Microbiology - Anton G. Kutikhin (Frontiers Research Topics, 2015)
This collection represents certain discoveries that were made in evolutionary and genomic microbiology during the recent ten years. We attempted to shed light on topical issues of microbial evolution and microbiome biology. In our eyes, these articles are of an excellent quality and may be helpful both for casual readers and for specialists in the field.